The Role of the Indonesian Waqf Board (BWI) in Productive Waqf in Gorontalo Province - Miranti Midu; Fatmawati N. Halid; Syaifuddin Podungge; Hussein Azeemi Abdullah Thaidi; Ibah Misbah (Department of Sharia Financial Management, IAIN Sultan Amai Gorontalo, 2025)
Talaa : Journal of Islamic Finance Volume: 4 No:1 (page: 46–57)